2000
DOI: 10.1128/cdli.7.1.40-44.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Antigenic Sites 1 and 3 of Serotype 3 Poliovirus after Vaccination with Oral Live Attenuated or Inactivated Poliovirus Vaccine and after Natural Exposure

Abstract: Three important antigenic sites involved in virus neutralization on polioviruses in mouse experiments have been identified. These sites are located at the surface of the virion and have been designated antigenic sites 1, 2, and 3. In mice, the antibody response to antigenic site 1 of serotype 3 poliovirus is considered to be immunodominant, but little is known about the immunogenicity of these sites in humans. In the present study, we developed inhibition enzyme-linked immunosorbent assays specific for antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…2,3 However, the immunological effect achieved by the inactivated poliovirus vaccine in children requires large amounts of antigen and a proper immunization schedule, which has been improved continuously since its application in the 1990s. 4 The global action plan for poliomyelitis eradication that was drafted by the World Health Organization (WHO) recommended using the inactivated poliovirus vaccine of the Sabin strain (sIPV) in developing countries; however, concerns were raised regarding the immune patterns of sIPV, and intradermal inoculation was suggested to achieve better immune effects with smaller amounts of antigen. 5,6 In fact, some data on intradermal immunization with IPV were positive and indicated that immunological studies would be useful for the development of novel inactivated enterovirus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, the immunological effect achieved by the inactivated poliovirus vaccine in children requires large amounts of antigen and a proper immunization schedule, which has been improved continuously since its application in the 1990s. 4 The global action plan for poliomyelitis eradication that was drafted by the World Health Organization (WHO) recommended using the inactivated poliovirus vaccine of the Sabin strain (sIPV) in developing countries; however, concerns were raised regarding the immune patterns of sIPV, and intradermal inoculation was suggested to achieve better immune effects with smaller amounts of antigen. 5,6 In fact, some data on intradermal immunization with IPV were positive and indicated that immunological studies would be useful for the development of novel inactivated enterovirus vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the lowest amount of antibody against site 1 was detected in O 1 K-vaccinated cattle; this could be due to the small sample size for this vaccine or because these five cattle were the only animals that received a booster dose on day 21 following vaccination. Herremans et al (2000) also observed a change in site-specific dominance associated with booster vaccination, finding a relative rise in the level of antibody to site 3 in poliovirus. In the case of the O 1 BFS group, 9 % of animals had approximately equal levels of antibodies against sites 1 and 2 ().…”
Section: Full Textmentioning
confidence: 80%
“…IPV has also been used in supplementary immunization activity (SIA) to control outbreaks and accelerate poliovirus eradication in endemic countries [ 11 , 12 ]. Vaccination with only IPV was apparently inferior as measured by fecal shedding after challenge, but reportedly had different outcome when administered subsequent to doses of OPV [ 13 , 14 , 15 ]. Although many of these studies support the use of IPV after OPV, the timing of IPV and the effect of it on mucosal protection represented a knowledge gap.…”
Section: Introductionmentioning
confidence: 99%